2010
DOI: 10.1016/j.dental.2010.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Properties of methacrylate–thiol–ene formulations as dental restorative materials

Abstract: Objectives-The objective of this study was to evaluate ternary methacrylate-thiol-ene systems, with varying thiol-ene content and thiol:ene stoichiometry, as dental restorative resin materials. It was hypothesized that an off-stoichiometric thiol-ene component would enhance interactions between the methacrylate and thiol-ene processes to reduce shrinkage stress while maintaining equivalent mechanical properties.Methods-Polymerization kinetics and functional group conversions were determined by Fourier transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 40 publications
2
76
0
2
Order By: Relevance
“…The covalent interaction of the thio-urethane with the methacrylate occurs through chain-transfer to the pendant thiol functionalities on the backbone of the oligomer. Those chain-transfer reactions delay the gelation/vitrification to higher degrees of conversion [37,38] while at the same time reducing stress development and improving network homogeneity and fracture toughness [2527]. For all of those reasons, the incorporation of thio-urethane oligomers into methacrylate networks used for dental materials applications is very promising.…”
Section: Discussionmentioning
confidence: 99%
“…The covalent interaction of the thio-urethane with the methacrylate occurs through chain-transfer to the pendant thiol functionalities on the backbone of the oligomer. Those chain-transfer reactions delay the gelation/vitrification to higher degrees of conversion [37,38] while at the same time reducing stress development and improving network homogeneity and fracture toughness [2527]. For all of those reasons, the incorporation of thio-urethane oligomers into methacrylate networks used for dental materials applications is very promising.…”
Section: Discussionmentioning
confidence: 99%
“…19 More recent studies have shown no significant changes in DC over 48 h post-irradiation 20 and a plateau in polymerization kinetics within minutes postirradiation. 21,22 Truffier-Boutry et al 20 suggested that postpolymerization changes in material properties should not be associated with ''a simple chemical process'' of continued polymerization and proposed that polymers physically shrink The same superscript letters indicate no statistically significant difference between time intervals in each group ( p > 0.05). due to excess of free volume, bringing free radicals closer which may result in limited propagation and termination.…”
Section: Group 2: Tpo / Blue Polymentioning
confidence: 99%
“…Wet polishing was applied since it has been shown to have no effect on DC values 20) . Micro-Raman analysis was done within 10 min post-polymerization since studies on polymerization kinetics of various resin models and RBCs have shown a plateau in conversion within minutes of the start of polymerization [21][22][23] . The present results have shown a logarithmic relationship between the amount of Lucirin ® TPO and the resultant DC for both unfilled and filled resins.…”
Section: Discussionmentioning
confidence: 99%